Incidence of Candida spp. mucosal oral patients infected by Human Immunodeficiency (HIV) in Santo Angelo-RS - Hartmann, Andreia (2016)
Background and Objectives: Currently, there is an increase in fungal infections, especially in immune compromised patients. Among the fungi that cause invasive infections there is the yeast of the genus Candida, considered HIV progression marker. Antifungal therapy and diagnosis are important for the treatment of oral candidiasis, due to the resistance attributed to certain species. Thus, the aim this study was to determine the incidence of oral candidiasis in patients with the HIV virus, to define the species, the virulence factors and sensitivity to fluconazole. Methods: Researched to colonization of the oral mucosa of HIV-positive patients with the aid of a sterile swab and culture in Sabouraud Dextrose Agar. The activity of proteinase and phospholipase were done. Susceptibility testing was performed by disk diffusion method. A record filled with socio-economic data, and clinical information regarding medications and symptomatology of patients. Results: The sample was consisted of 45 people. The average age of patients was 38 years (± 13.63). The rate of oral colonization by Candida in HIV patients was 53.3%, of these, 95.83% owned by albicans species. The isolates showed positive activity and strongly positive for phospholipase and proteinase. In the susceptibility test showed 25% of the isolates were resistant to fluconazole. Conclusion: Early diagnosis of candidiasis in HIV-infected patients is essential both for the immediate treatment, and to improve their quality of life, since the thrush is a very common oral lesions in this population.